Analisis Loyalitas Konsumen Terhadap Minuman Kopi Robusta Di Kota Banda Aceh - Rahmaddiansyah Rahmaddiansyah; Fajri Fajri; Cut Vania Utami (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2015)
ABSTRACT. Coffea is one of the biggest enthusiasts beverage in the world. It had been proven by the increases of coffea production. Robusta coffea is one kind of the most marketed beverage in Banda Aceh. The aim of this study is to know the factors that affected the consumer loyalty toward robusta coffea drinks and the relations between consumer satisfaction and consumer loyalty toward robusta coffee drinks in Banda Aceh. The analysis in this study employed Binary Logistic regression. The result of Binary Logistic showed that the taste and price of robusta coffea drinks were the factors that affected consumer loyalty toward robusta coffea drinks. The result of Chi-Square test showed that there were the significant relations between consumer satisfaction and consumer loyalty toward robusta coffea drinks in Banda Aceh.